1978
DOI: 10.1056/nejm197810122991501
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin Analogues Are Present in Human Plasma and Can Mask Cobalamin Deficiency because Current Radioisotope Dilution Assays Are Not Specific for True Cobalamin

Abstract: Since R protein binds cobalamin (vitamin B12) and cobalamin analogues, whereas intrinsic factor is highly specific for true cobalamin, we compared the serum cobalamin values obtained with these proteins in radioisotope dilution assays. With R protein, eight of 21 patients with cobalamin deficiency had serum cobalamin levels (mean, 204, range, 85 to 355 pg per milliliter) that overlapped with values for 74 normal subjects (mean, 576, range, 220 to 1230). With intrinsic factor, no patient values (mean, 36, range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(97 citation statements)
references
References 19 publications
3
92
1
1
Order By: Relevance
“…Our results showed that measured holoHC was approximately twice as high as calculated holoHC. This supports the presence of analogues on HC 8 and suggests that the amount of analogues bound to HC increased during pregnancy. At present, we have no explanation to offer for this observation.…”
supporting
confidence: 75%
“…Our results showed that measured holoHC was approximately twice as high as calculated holoHC. This supports the presence of analogues on HC 8 and suggests that the amount of analogues bound to HC increased during pregnancy. At present, we have no explanation to offer for this observation.…”
supporting
confidence: 75%
“…Blood collections were performed for measurement of total serum vitamin B 12 (9,10) and holoTCII in all subjects at weekly intervals for the first month and at monthly intervals for 4 months. After 3 months of metformin therapy, oral calcium carbonate (1.2 g/day) was administered to the metformin group alone for 1 month.…”
Section: Subjectsmentioning
confidence: 99%
“…After separation, serum samples were frozen immediately at Ϫ20°C until assayed (Simul-TRAC; Becton Dickinson, Orangeberg, NY). Vitamin B 12 and vitamin B 12 analogs were assayed by differential radioassay according to the modification by Kolhouse et al (9) of the method of Lau et al (10) using purified IF to measure cobalamin and R-binder to measure total corrinoids (9,10). The analogs are measured by the difference between the 2 assays; elevated levels of the analogs indicate bacterial overgrowth of the small intestine, except in rare cases of ingestion of the analogs themselves from alternative medicine sources, e.g., herbs, algae, or seaweed.…”
Section: Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both transcobalamin and intrinsic factor bind cobalamin in a base-on conformation, whereas the binding mode for haptocorrin depends on the lower axial ligand. In addition to cobalamins, haptocorrin can bind cobinamides, B 12 analogs that lack the DMB moiety, cannot be converted to the active cofactor forms by mammals, and account for ϳ40% of the total plasma corrins (29). Although a definitive role for haptocorrin remains to be established, its suggested functions include a role in B 12 storage and in removal of inhibitory corrinoid derivatives.…”
Section: Absorption Transport and Storage Of Cobalaminmentioning
confidence: 99%